Health Disaster Preparedness Using Android Mobile Based Application Case Mount Bromo Eruption - Mukhamad Fathoni; Fadly Usman; Septiana Hariyani; Eddi Basuki Kurniawan; Ah Yusuh; Christrijogo Soemartono Waloejo (Jurnal Ners, 2020)
Introduction: In the last 10 years, Mount Bromo has erupted four times; 2004, 2010, 2015 and 2019. However, it is unique that people at Tengger are reluctant to evacuate even though Mount Bromo is erupting and releasing volcanic material such as stones and dust.Methods: This research is a quantitative study, using correlative analytic observational design and cross sectional approach with pourposife sample of 120 taken from online questionare results of bivariate analysis using gamma correlation test obtained the results of knowledge factors (p=0.005; r=0.27) attitude (p=0.000; r=0.45), means of infrastructure (p=0.000; r=0.58), and android application (p=0.000; r=0.59) for health preparedness. Results: Knowledge, attitude, infrastructure and android application factors can influence health preparedness in disaster risk reduction in Bromo area.Using the smartphone application as the Mount Bromo information facilities are one of an effort so that people and tourists can activate if an eruption occurs. There is important health preparedness about features made in the application such as distribution shelters, evacuation routes, health centres, photos, videos, and primary health care information.Conclusion: Assessment results to the application interface, the information conveyed, and the features offered showed that the application was very useful and gives a new perspective in conveying accurate information to the public and also tourists. The health preparedness community level is also quite good with the services provided by the Bromo alert application.